Effect of hydrodynamic parameters on nickel removal rate from wastewater by ion flotation. (15th August 2019) - Hoseinian, Fatemeh Sadat; Rezai, Bahram; Safari, Mehdi; Deglon, David; Kowsari, Elaheh
Abstract: This study investigated the effect of hydrodynamic parameters on the nickel ion removal in an oscillating grid flotation cell (OGC) with near ideal hydrodynamic environments. Nickel ion was removed in the OGC at various energy inputs (0–2 W/kg), using two bubble sizes (130 and 820 μm) at three surfactant concentrations (SDS/Ni(II) ratio of 1–3) and three air flow rates (1–3 L/min). The results indicated that the energy input has a considerable effect on the ion flotation kinetics and recovery and it is strongly dependent on the cell types (contact environment) and bubble size. Increasing energy input led to an increase in the nickel removal rate due to an increase in the collision rate for bigger bubbles and an optimum flotation rate for smaller bubbles. Nickel removal rate increased around 80% (1.8 times) with an increase in energy input from 0 to 2 W/kg for both bubble sizes. Increasing air flow rate generally led to an increase in the nickel removal rate. A comparison of the effect of energy input on the nickel removal separation efficiency in two different hydrodynamic environments showed that the isotropic and homogeneous contact environment in the OGC is more appropriate than anisotropic and inhomogeneous turbulence in the mechanical cell for ion removal using ion flotation. Graphical abstract: Image 1 Highlights: The overall treatment performance of the OGC was better than the mechanical cell. Increasing energy input has a major effect on the on the ion flotation kinetics. The energy input effect is strongly dependent on the cell types and bubble size. For smaller bubbles, increasing energy input leads to an optimum Ni(II) removal rate. There is a linear trend of Ni(II) removal rate along with an increase of gas flow rate.